2014
DOI: 10.3109/21681805.2014.990052
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and partner-specific quality of life in partners of men with lower urinary tract symptoms compared with partners of men from the general population

Abstract: The partner-specific quality of life was impaired in partners of men with LUTS suggestive of BPO. Sleep and HRQoL did not differ between partners of men with LUTS and partners from the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The 2006 U.S. National Health and Wellness Survey data showed that LUTS is significantly associated with increasing emergency room visits, doctor visits, and hospitalizations (odds ratios: 1.57, 1.52, and 1.56, respectively), as well as greater loss of work productivity (8.03%) than normal controls (Kannan, Radican, Turpin, & Bolge, 2009). Evidence has shown that QOL in the caregivers and partners of men with LUTS was impaired (Gotoh et al., 2009; Marklund, Spångberg, & Edéll-Gustafsson, 2014). It was estimated that BPH alone cost $1.1 billion annually in 2000 in the United States (Wei et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The 2006 U.S. National Health and Wellness Survey data showed that LUTS is significantly associated with increasing emergency room visits, doctor visits, and hospitalizations (odds ratios: 1.57, 1.52, and 1.56, respectively), as well as greater loss of work productivity (8.03%) than normal controls (Kannan, Radican, Turpin, & Bolge, 2009). Evidence has shown that QOL in the caregivers and partners of men with LUTS was impaired (Gotoh et al., 2009; Marklund, Spångberg, & Edéll-Gustafsson, 2014). It was estimated that BPH alone cost $1.1 billion annually in 2000 in the United States (Wei et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…While patients and their partners were not asked whether they were living under the same roof, or sharing the same bed, bed sharing is a common practice. There is growing evidence suggesting that a sleep disorder in 1 partner may increase risk for a sleep disorder in the other partner, all the more so when 1 partner is affected by a condition associated with a sleep disorder (26,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Nocturia, in particular, negatively affects sleep, increases fatigue, and adversely impacts the quality of life (29). Moreover, nocturia may also lead to a decline in the quality of life of patients' partners (30). Therefore, treatment of nocturia is also a focus of BPH treatment, but the effectiveness of the drugs, tamsulosin and finasteride, in treating nocturia is limited (31).…”
Section: Discussionmentioning
confidence: 99%